Great ball of light - Kuhlman, Evan; Holmes, Jeremy (Atheneum, 2015)
When a ball of light appears with the power to bring the dead back to life, twins Fiona and Fenton are determined to catch it and perform some experiments
"Jerry Holmes is crossed out and replaced with "Fiona North."
Keywords: Dead; Brothers and sisters; Twins; Kinderbuch